2014
DOI: 10.5935/0034-7280.20140046
|View full text |Cite
|
Sign up to set email alerts
|

Increased intercellular adhesion molecule-1 immunoreactivity in the sclera-choroid complex in hypercholesterolemia experimental model

Abstract: Aumento da imunorreatividade da molécula de adesão intercelular-1 na esclera e coroide em modelo experimental de hipercolesterolemia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…At the end of 12 weeks, animals were sacrificed at the animal surgical laboratory of central research and animal facility, International Islamic University Malaysia (CREAM)-IIUM. Induction of general anaesthesia was done by intramuscular injection of a combination of ketamine and xylazine [ 28 ] at doses of 50 mg/kg and 10 mg/kg, respectively [ 29 ]. Laparotomy and sternotomy were performed for full exposure of liver [ 30 ], and then through left ventricular approach, systemic perfusion was secured by infusion of ice-cold normal saline and euthanasia was achieved by exsanguination of blood through opened right atrium [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the end of 12 weeks, animals were sacrificed at the animal surgical laboratory of central research and animal facility, International Islamic University Malaysia (CREAM)-IIUM. Induction of general anaesthesia was done by intramuscular injection of a combination of ketamine and xylazine [ 28 ] at doses of 50 mg/kg and 10 mg/kg, respectively [ 29 ]. Laparotomy and sternotomy were performed for full exposure of liver [ 30 ], and then through left ventricular approach, systemic perfusion was secured by infusion of ice-cold normal saline and euthanasia was achieved by exsanguination of blood through opened right atrium [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The decision to euthanize rabbits of the NG group after 4 weeks was made based on the results of earlier studies (24,35) . We have demonstrated that cholesterol-enriched diet induces an increase in macrophage concentration in the choroid-sclera com plex, causing thickness of these structures (24,25,35) . The diet also induced hypoxia of the retinal tissue, leading to neuronal damage (35) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, rabbits were fed with cholesterol enriched diet to evaluate the expression of the TNF-α and IL-6 in the choroidscle ral complex. It has been reported that cholesterol-enriched diet induces hypoxia of the retinal tissue (24) , increase in the macrophage concentration in the choroid and sclera (24)(25) , as well as increase in A B Figure 2. Immunoreactivity of choroid and sclera to IL-6 antibody.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations